Landscape Topography and Regional Drought Alters Dust Microbiomes in the Sierra Nevada of California - Maltz, Mia R.; Carey, Chelsea J.; Freund, Hannah L.; Botthoff, Jon K.; Hart, Stephen C.; Stajich, Jason E.; Aarons, Sarah M.; Aciego, Sarah M.; Blakowski, Molly; Dove, Nicholas C.; Barnes, Morgan E.; Pombubpa, Nuttapon; et al. (Frontiers in Microbiology, 2022)
Dust provides an ecologically significant input of nutrients, especially in slowly eroding ecosystems where chemical weathering intensity limits nutrient inputs from underlying bedrock. In addition to nutrient inputs, incoming dust is a vector for dispersing dust-associated microorganisms. While little is known about dust-microbial dispersal, dust deposits may have transformative effects on ecosystems far from where the dust was emitted. Using molecular analyses, we examined spatiotemporal variation (throughout two dry seasons) in incoming dust microbiomes along an elevational gradient within the Sierra Nevada of California. We found that dust microbiomes differed by elevation across two summer dry seasons (2014 & 2015), which corresponded to competing droughts in dust source areas. Dust microbial diversity decreased with elevation and was inversely proportional to dust heterogeneity. Likewise, dust phosphorus content increased with elevation. At lower elevations, early season dust microbiomes were more diverse than those found later in the year. The relative abundances of microbial groups shifted during the summer dry season. Furthermore, mutualistic fungal diversity increased with elevation, which may have corresponded with the biogeography of their plant hosts. Although dust fungal pathogen diversity was equivalent across elevations, elevation and sampling month interactions for the relative abundance, diversity, and richness of fungal pathogens suggest that these pathogens differed temporally across elevations, with potential implications for humans and wildlife. This study shows that landscape topography and droughts in source locations may alter the composition and diversity of ecologically relevant dust-associated microorganisms.